Analysis of wireless power transfer using resonant inductive coupling method - Mohamad, Khairul Anuar; Zulkefli, Ain Nazatul Nadia; Mohamad Nasir, Nor Atiqah; Alias, Afishah (Penerbit UTHM, 2020)
Nowadays, the wireless power transfer technology receives intense attention among the people, especially the people who like to travel or always use gadget. It is a technology that exploits electromagnetic, magnetic and electric field to transmit electric power without conductor which eliminates the use of current carrying wires. As wearable technology becoming increasingly integrated into our daily lives, an innovative electrical supply is required to ensure power is supplied in more manageable, comfortable and safe without charging using wires. The wireless power transfer offers convenient application with variety of method to transfer the electrical energy instead used the connecting wires. There are several approaches for transferring the electric power wirelessly. Wireless power transfer methods are divided into two categories according to the distances of the transmitted power which are near-field and far-field techniques ...